IMPLEMENTATION OF TOLERANCE AND MUTUAL COOPERATION VALUES IN STRENGTHENING CHARACTER EDUCATION FOR CHILDREN AT THE KAMPUNG BHARU MALAYSIA GUIDANCE CENTER - Cindy Safira; Ryan Taufika; Hotma Siregar; Miftha Huljannah; Heru Sanjaya; Juliaman Siahaan (Program Pascasarjana UIN Sumatera Utara, 2026)
The importance of character education in Indonesia aims to create social harmony in the midst of the diversity of Southeast Asia, where tolerance means respecting differences and mutual cooperation involving group cooperation. The purpose of this study is to explore the application of the values of tolerance and mutual cooperation to strengthen character education in children at the Kampung Bharu Guidance Studio, Malaysia, a non-formal institution that serves children from migrant families. The research method uses descriptive qualitative methods, research is conducted through participatory observation, semi-structured interviews with studio managers, and documentation of activities from September to October 2025. The findings in this study reveal that the values of tolerance and mutual cooperation are instilled through routines such as scouting activities, mutual cooperation to clean the environment, and morning moral coaching. The manager acts as a role model by showing a polite and empathetic attitude, while parental participation through communication and collaboration groups reinforces the consistency of values between the studio and the home. This conclusion emphasizes that informal studios manage to positively shape the character of migrant children. This research contributes to the development of an inclusive character education literature, and supports education policies that are sensitive to local contexts.